2015
DOI: 10.1080/21645515.2015.1058456
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of pneumococcal infections during mass gathering

Abstract: The interest in mass gathering and its implications has been increasing due to globalization and international travel. The potential occurrence of infectious disease outbreaks during mass gathering is most feared. In this context, respiratory tract infections are of great concern due to crowding in a limited space which facilitates and magnifies the potential of disease spread among attendees. Pneumococcal disease is best described among pilgrims to Makkah and vaccination is one of the methods for the preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Wearing masks especially when in crowded places, frequent hand washing with soap and water or disinfectant, especially after coughing and sneezing, and the use of disposable handkerchiefs are recommended by the Saudi Ministry of Health [24]. Only 8.4% of the Hajj pilgrims wore masks during the H1N1 outbreak in 2009 and less than 1% wore masks during the MERS-CoV epidemic in 2013 [5]. In our survey, cough, fever and antibiotic consumption were significantly more frequent in individuals using face masks, which likely accounts for the high willingness of pilgrims suffering from febrile cough to wear a face mask, with the aim of avoiding spreading diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Wearing masks especially when in crowded places, frequent hand washing with soap and water or disinfectant, especially after coughing and sneezing, and the use of disposable handkerchiefs are recommended by the Saudi Ministry of Health [24]. Only 8.4% of the Hajj pilgrims wore masks during the H1N1 outbreak in 2009 and less than 1% wore masks during the MERS-CoV epidemic in 2013 [5]. In our survey, cough, fever and antibiotic consumption were significantly more frequent in individuals using face masks, which likely accounts for the high willingness of pilgrims suffering from febrile cough to wear a face mask, with the aim of avoiding spreading diseases.…”
Section: Discussionmentioning
confidence: 99%
“…6,17 This is concerning because pneumonia is the leading cause of hospital admission and an important cause of mortality at Hajj. [18][19][20] Furthermore, surveys have shown that many pilgrims were not aware that pneumonia is transmissible 21 and preventable by vaccination. 22 There is currently no formal guidance from the Saudi MoH on the use of pneumococcal vaccine for Hajj pilgrims, which may partly explain this apparent lack of awareness (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The available literature shows that 7-37% of pilgrims are older adults (≥65 years of age), and that the compliance with age specific pneumococcal vaccine among pilgrims is 5% [59]. In a recent review, the carriage of pneumococcal vaccine serotype was higher in the post-Hajj period compared to the pre-Hajj period [60].…”
Section: Pneumococcal Diseasementioning
confidence: 99%